2020
DOI: 10.1080/2162402x.2020.1773205
|View full text |Cite
|
Sign up to set email alerts
|

Standard therapies: solutions for improving therapeutic effects of immune checkpoint inhibitors on colorectal cancer

Abstract: Immunotherapy using immune checkpoint inhibitors has opened a new era for cancer management. In colorectal cancer, patients with a phenotype of deficient mismatch repair or high microsatellite instability benefit from immunotherapy. However, the response of rest cases to immunotherapy alone is still poor. Nevertheless, preclinical data have revealed that either ionizing irradiation or chemotherapy can improve the tumoral immune milieu, because these approaches can induce immunogenic cell death among cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…For example, previous work has shown that EGFR inhibitor erlotinib improves the efficacy of anti–PD-1 antibody in EGFR -mutated non–small cell lung cancer by decreasing CD4 + effector T reg infiltration in the TME ( 52 ). In colorectal cancers, anti-EGFR therapy in combination with chemotherapy results in increased cytotoxic T cell infiltration ( 54 ), leading some to argue that anti-EGFR treatments should be combined with ICIs in this cancer ( 55 ). That said, we are the first to offer a likely mechanism of action for these observations, including the central role of immunosuppressive chemokines and EGR1, both of which can serve as potential biomarkers for patient selection in other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous work has shown that EGFR inhibitor erlotinib improves the efficacy of anti–PD-1 antibody in EGFR -mutated non–small cell lung cancer by decreasing CD4 + effector T reg infiltration in the TME ( 52 ). In colorectal cancers, anti-EGFR therapy in combination with chemotherapy results in increased cytotoxic T cell infiltration ( 54 ), leading some to argue that anti-EGFR treatments should be combined with ICIs in this cancer ( 55 ). That said, we are the first to offer a likely mechanism of action for these observations, including the central role of immunosuppressive chemokines and EGR1, both of which can serve as potential biomarkers for patient selection in other tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 255 , 260–263 Yet, as of now the difficulty in generating cDC1/2 from patients in large amounts remains a hurdle for cDC-based DC vaccinations. Simultaneously, DC vaccine research also needs to account for challenges that are also plaguing success of ICBs in the clinic, e.g., deep immunosuppressive niches within the TME of lymphocytes-depleted solid tumors, 249 , 264–266 adaptive or acquired emergence of antigen-loss variant versions of cancer cells, 267–270 and the patient-to-patient immune heterogeneity (owing to immune haplotypes, archetypes, ethnicities, as well as microbiome variations). 271 , 272 Manufacturing and production costs associated with DC vaccines also need to be considered and reduced, possibly through higher automation, to ease overall practicability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a phase II study reported that as a second- or later-line therapy for metastatic PDAC, durvalumab (an anti-PD-L1 drug) alone and durvalumab plus tremelimumab (an anti-cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) drug) had objective response rate (ORR) values of 0% and 3.1%, respectively [ 56 ] ( Table 2 ). Prior to this study, in order to improve the effectiveness of ICB therapy, a phase I study employed stereotactic body radiation therapy (SBRT) in combination with ICB therapy (in this case pembrolizumab) to upregulate the expression of the genes encoding PD-L1 and MHC-I in tumor cells and improve the production of tumor-associated antigens (TAAs) by recruiting tumoricidal T cells and by improving the production of IFN-γ by CD8 + T cells [ 18 ] as a strategy against metastatic cancers, and this combination achieved an ORR of 13.2% among enrolled patients [ 57 ]. However, this study only included three patients with metastatic PDAC, and their ORR to this strategy was not reported.…”
Section: Current Status Of Immune Checkpoint Blockade Therapy For Pdacmentioning
confidence: 99%
“…Similarly, KRAS mutation is able to cause immunosuppression in CRAC tumors as well. However, unlike in PDAC, the published data suggest that CRAC patients with this phenotype can benefit from a combinational strategy featuring conventional therapy plus an ICB drug [ 18 ]. Importantly, despite having KRAS mutation, PDACs, CRACs and LUACs differ in their tumor immune status ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%